Smart Board Live Application: Super Complete Online Learning Platform for Effective Online Learning - Nilam Cahyati; Meli Asma Desti; May Sari (The Faculty of Teacher Training and Education The University of Jember Jember, Indonesia, 2021)
Online learning in Indonesia currently has many obstacles. Some of the obstacles are less supportive learning device, participants find it difficult to download various applications to support online learning, and the difficulty of educators when explaining calculation material and formulas online. So, we provide solutions in the form of user interface design in the application that we design, namely Smart Board Live. This paper is made using quantitative descriptive data and literature studies. The design of this application will provide all the features needed to support teaching and learning activities. In this application there are some menu; Live Board, Attendance List, Exam, Collection of Materials, Student Assignment, and Account. The Live Board menu is the main menu in the form of an interactive digital whiteboard that can make interconnect users, brainstorm, write, draw, visualize ideas, record, share documents, and share editing and additions made on the board.